Parametric Production Planning - Jones, Curtis H. (Management Science, 1967)
This paper proposes a heuristic approach to the determination of work force and production levels. The existence of two feed-back rules (one for work force and one for production) is postulated. The universe of possible parameters is searched to find the set of parameters that provides the lowest cost or highest profit for a particular firm. Each set of parameters is evaluated by comparing the costs or profits resulting from the application of rules bearing these parameter values to a likely sequence of sales forecasts and actual sales. Decision rules formed in this way give cost and profit results nearly equal to those resulting from the application of the optimal techniques to purely mathematical problems. In more complex and more realistic situations, the results obtained by Parametric Production Planning may be superior to those achieved by a linear programming approach or a linear decision rule.